PERJUANGAN MENCARI RUANG: Jedoran, Media Islamisasi, Dan Peminggiran Kesenian Islam Tulungagung 1970-1982 - Hanifah, Muna Roidatul (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2021)
This study is a concrete effort to trace the dynamics of Jedoran Tulungagung 1970-1982. Thistemporal term became the starting point for the paradigm shift of the Tulungagung people in interpretingIslamic art. The emergence of the 'Popular' prayer reduced the public's interest in Jedoran as anacculturative (Islamic and Javanese) shalawat art which has contributed to the history of Islamizationin Tulungagung. The study used historical research methodologies, namely: heuristics, source criticism,interpretation, and historiography. The results of this study indicate that there is one major narrativethat masterminds the dim existence of Jedoran from the Tulungagung art scene. This factor was the entryof the â€œPopular Islamâ€ paradigm, which at that time was rapidly developing through radio, televisionand mobile phones in almost all parts of Indonesia. This has gradually resulted in the decline in people'sappetite for acculturative Islamic arts such as Jedoran. This factor is supported by two other situations,namely the cultural atmosphere in Tulungagung in general after 1965 and the difficulty in studyingJedoran which makes regeneration difficult.